Pedal Power Energy Harvesting - Sah Azmi, Syeikh Muhammad Haziq (Universiti Sains Malaysia, 2018)
Renewable energy plays an important role in reducing greenhouse gas emissions such as biofuels, solar, and wind. They are favorable and located in remote area. For example, on cloudy days or when any disaster phenomenon occurs solar is not an efficient way to harvest energy and leads to where the victim of the disaster cannot reach for electricity. The temporary energy keeps used by the user until it’s drain out. Therefore, this project proposes generate our own power by cycling during emergency situation happened. This project was inspired based on Hurricane Maria which devastated the small town in the mountains of central Puerto Rico, where the hurricane downed power lines throughout the area. The conversion of food energy to external mechanical energy during physical activity has efficiencies in the range of 2.6 - 6.5%, depending on the type of physical activity being performed. Out of the variety of energy recovery techniques that exist, pedal motion electricity generation shows the most promise for large-scale recovery. The voltage produced is up to 15V to 30V. However, due to that output voltage produce by the generator is more than battery charging requirement, a voltage regulator is need to be included to regulate the voltage generated by permanent magnet direct current generator to a certain voltage and current level so it can be readily use to charge up the battery without harm it. An Arduino Mega is used as controller to isolate the speed and voltage in order to control the cut off voltage when the battery is full. In the end, the effect of different speed of pedaling on electrical production is also investigated. In the end of this research, it is found that slow cycling speed gives high efficiency to harvest energy, but took long time to full charge the battery. The amount of power generated at this condition was 7.392W. This amount of energy enough to charge up mobile phone, light up low power LED light and fan during emergency situation.